Historias contagiosas en épocas de pandemia - Pineda Arroyave, Brigit (Universidad Católica Luis Amigó, 2021)
This book will be kept in the collective memory. It is the record of how much we underestimate the power of words, that is until we come up close with the term pandemic. Language has shown us its strength in these eight letters, which weave a web of dualities: they divide us, but they unite us; they distress us and, in contrast, fill us with hope; they bring us back to simplicity and require us to project ourselves. Words are also the means to talk about emotions that the virus has overwhelmed and that readers who come to this book want to express. It is a way of understanding the present and the future the public health situation that so many countries of the world go through and a means to understand ourselves and put ourselves in the place of others. Will it be that you will feel identified with any of the authors? Surely yes.